Motivation in Mathematics Learning - A A N Fuqoha; Budiyono Budiyono; D Indriati (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
The purpose of this research is to know the motivation of mathematics learning in high school students of 10th grade. Data collection method is done in the form of survey conducted in Purbalingga. The instrument used is a questionnaire of motivation to learn math. Interview method is also done to get additional data which is used as supporting data in conducting analysis of data obtained previously. The result of the survey shows that the students of both schools have a high motivation to learn math with an average of 3.39. Based on the results of the analysis, a lot of the students who have high learning motivation on math dissatisfied with the value of daily tests and examinations with an average index of 2.31. It shows that high learning motivation is not enough to get a satisfactory value. The statement was corroborated by points on the understanding of mathematical material that was only able to obtain an average index of 2.56. Based on the results of interviews from 3 students, they wanted to use a good learning media that had three characteristic, that was a learning media that taught students not to give up easily, that was able to bring out a sense of pleasure, and that was challenging. Therefore, beside high learning motivation, understanding of mathematics materials supported by the use of good learning media is also required.